Socialization Of Reproduktive and Sexual Health Problems In Adolescent In SMA Negeri 2 Kota Tegal - Intan Monik Pratami (INSTITUT KESEHATAN DELI HUSADA, 2022)
Adolescents are part of a society that is undergoing a transition process from childhood to adulthood. During the transition period, there are many changes, both physically and psychologically. Reproductive health is a state in which physical, mental and social well-being, intact and not merely free from disease or disability in all matters relating to the reproductive system, function and process . During adolescence, there are striking changes physically and psychologically which is commonly referred to as puberty. The purpose of this socialization is so that teenagers can apply healthy behavior patterns, namely avoiding early marriage, sex before marriage or free sex, and avoiding the abuse of narcotics, psychotropic substances and addictive substances. The method used to increase the knowledge of adolescents is by socializing or counseling. The author hopes that after this counseling or socialization is carried out, adolescents can find out how important it is to maintain reproductive health. The expected result is an increase in adolescent knowledge about the importance of reproductive health in adolescents at SMA Negeri 2 Kota Tegal